Interferences and asymmetries in laser-assisted photoionization of diatomic molecules - Boll, Diego I. R. (2014)
Several kinds of interference effects in laser-assisted photoionization of H2+ molecular targets are theoretically investigated by means of a Coulomb-Volkov model. The photoelectron angular distributions in the single-photon ionization reaction are compared to more elaborated results, and the influence of usual approximations are studied. Several configurations of pulses and assistant lasers are considered. Moreover, we show that previous interference effects predicted for monochromatic pulses could be enhanced and/or diminished leading to a directional selectivity of photoelectron emission. Finally, we analyze the influence of the pulse duration on the photoelectron spectrum.